A Pharmacokinetic and Safety Study of Trebananib, an Fc‐Fusion Peptibody, in Patients With Advanced Solid Tumors and Varying Degrees of Renal Dysfunction. Issue 2 (9th June 2017) - Wu, B; Lewis, LD; Harvey, RD; Rasmussen, E; Gamelin, E; Sun, Y‐N; Friberg, G; Koyner, JL; Dowlati, A; Maitland, ML
Abstract : Clearance of trebananib (AMG 386), a 64‐kD antiangiogenic peptibody, has been associated with estimated glomerular filtration rate (eGFR). We prospectively evaluated trebananib pharmacokinetics and safety/tolerability in advanced solid tumor patients with varying degrees of renal function. Patients were assigned to normal renal function, mild, moderate, or severe renal dysfunction cohorts based on eGFR, received trebananib 15 mg/kg i.v. weekly, and underwent week 1 and week 5 pharmacokinetic and weekly safety assessments. For 28 patients, trebananib clearance decreased from normal renal function (1.52 mL/hr/kg), to mild (1.20 mL/hr/kg), moderate (0.79 mL/hr/kg), and severe (0.53 mL/hr/kg) renal dysfunction ( P ≤ 0.001). Treatment‐related adverse events showed no association with clearance. Trebananib clearance was proportional to eGFR and unrelated to pretreatment protein excretion. These data confirm a role for renal clearance of a recombinant peptibody with molecular weight <69 kD and support a longer dosing interval for patients with severe renal dysfunction.